Alat Pendeteksi Jatuh pada Lansia dalam Keadaan Rawat Jalan Berbasis Internet of Things (IoT) - Eriska, Septia; Madiza Arradea, Muhammad Rezi; Zanu Saputra; Khasanah, Nur (Jurnal Inovasi Teknologi Terapan, 2025)
Falls among elderly individuals pose a serious risk, potentially leading to injuries or death. This study presents a real-time fall detection device integrated with the Internet of Things (IoT) to notify caregivers promptly. The device employs the MPU6050 sensor for movement and orientation detection, and the MAX30100 sensor for monitoring heart rate and blood oxygen saturation. Data from these sensors are processed using an ESP32 microcontroller and transmitted to a mobile application developed with MIT App Inventor. Testing results indicate high accuracy, with the deviceachieving a 93% succes rate in detecting various fall scenarios and over 97% accuracy in health parameter measurements. Notifications are delivered with in an average of 4.8 seconds, demonstrating its effectiveness in real-time monitoring. This development aims to improve the quality of life for elderly individuals through continuous health monitoring and rapid response to fall incidenst.